Analysis of the Effect of Household Consumption, Domestic Investment, Regional Expenditure, and Labor on Economic Growth in Five Regencies/Cities in West Java - Andayani, Sherliy Veri; Setiawati, Ririt Iriani (Indonesian Journal Publisher, 2025)
This study examines the impact of household consumption, domestic investment (PMDN), regional expenditure, and labor on the economic growth of the five largest regencies/cities in West Java during 2018–2023. Using secondary data from BPS, the analysis was conducted through panel data regression with the Fixed Effect Model (FEM), complemented by F and T tests. The results indicate that household consumption, PMDN, and regional expenditure have a positive and significant effect on economic growth, whereas labor does not show a significant impact. However, all four variables together have a significant influence. These findings highlight household consumption, PMDN, and regional expenditure as the main drivers of growth in West Java, while labor optimization remains important to enhance its contribution to sustainable regional development.